Ozadje uspešnosti potiska s prsi pri tekmovalcih triatlona moči - Reya, Matija (Šport (Ljubljana), 2018)
Bench press is considered one of the most recognisable and popular exercises for strength development and is commonly part of resistance training programmes. In addition to squat and deadlift, bench press is one of the three exercises performed in the sport of powerlifting. In this review we propose that the key determinants of 1-repetition-maximum (1 RM) bench press performance can be divided into three categories of factors. Firstly, 1 RM bench press performance is likely dependent on structural and anthropometric factors including body composition parameters and body segment lengths, widths and girths. Secondly, technique factors likely play a role in 1 RM bench press performance such as barbell and upper limb kinematics, the height of arch in the lumbar spine and the force production of the feet against the floor. Lastly, neuromuscular factors likely contribute to 1 RM bench press performance including voluntary muscle activation, muscle architecture and muscle activity of prime movers in different phases of the lift.
Keywords: dvigovanje uteži; potisk s prsi; tekmovalci; triatlon moči; uspešnost